Efficacy of robotic training gloves in improving hand function and movement in stroke patients - Abd Elhady Samy Abd Elhady; Gehan M. Ahmed; Amr Hassan; Saied Mohamed Ibrahim; Shaima Mohamed Abdelmageed (Sport TK)
Robotic training gloves are designed to assist with hand movements by providing resistance, support, or guidance. The efficacy of robotic training gloves on hand function in stroke patients, particularly when using the mirror mode, is an intriguing topic in rehabilitation therapy. This study aimed to investigate the effect of assistive robotic rehabilitation devices on hand function in stroke patients. A controlled randomized study was conducted with thirty (9 males and 21 female) stroke patients, who were selected from the outpatient clinic of Al-Delingat Central Hospital - Al-Buhaira Governorate. These patients were randomly assigned to two groups: the study group (A), which received the selected physical therapy program and mirror therapy assisted by a robotic rehabilitation glove, and the control group (B), which received only the conventional physical therapy program. When comparing between both groups, the results indicate that the patients in group A that underwent the combined therapy had a statistically significant improvement in grip strength when tested by the Jamar dynamometer (MD= 1.87 [0.39, 3.35], P=0.015) and in motor function when evaluated by the Fugl-Meyer scale than the group who had only conventional physical therapy (Group B) (MD= 16.67 [3.9, 29.4], p=0.012). This controlled randomized study provides evidence that combining robotic rehabilitation with a standard physical therapy program yields superior improvements in grip strength and motor function compared to standard physical therapy alone.